Manpower model for human resource planning management - Halim, Siti Sarah A.; Zeki, Akram M. (2012)
Human resource planning has traditionally been used by organizations to ensure that the right person is in the right job at the right time. The increasing of environmental instability, demographic shifts, changes in technology, and heightened international competition are changing the need for and the nature of human resource planning in leading organizations. Therefore, it is required to have a appropriate tool to assist management in order to present overview and visibility of manpower numbers by deciding the effect of variables on the optimal level of manpower force. This tool shall be the one-stop information gateway for users to achieve.